Analisis Fungsi Subbagian Humas Sekretariat Dewan dalam Meningkatkan Kinerja Dewan Perwakilan Rakyat Provinsi Aceh - Lestari, Aula; Husna, Cut Asmaul (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this study was to identify the function of public relations in the DPRA Secretariat in order to improve management performance. The extent to which the public relations sector of the DPRA secretariat has developed the existing public relations function into a more varied function with the aim of improving the relevant agencies is also studied in this study. The problem is focused on the performance of the public relations division of the Aceh Provincial DPRD. The method used in this study is a qualitative approach, where the procedures in the research produced are descriptive data, namely words or written answers from several sources and the results of direct observations in the field. Natural objects or natural settings are objects used in qualitative research which are often referred to as naturalistic research. Based on the results of the study, it can be concluded that the functions of the Public Relations, Protocol, and Publication Section of the Aceh DPR Secretariat have been carried out properly and in an orderly manner. The DPRA Public Relations Secretariat regulates its duties and functions slightly differently, but still in accordance with the applicable laws and regulations. This can be seen from the division of tasks and functions of public relations into several points, each of which has different and interconnected tasks and functions. Of course, public relations, protocols and publications have an impact on improving the performance of the Aceh DPR, but more specifically in this regard, consistency in fighting for people's aspirations and establishing relationships with the media in collaboration with the Aceh Provincial DPRD.